Grommets in otitis media with effusion: an individual patient data meta-analysis. Issue 5 (25th April 2005) - Rovers, M M; Black, N; Browning, G G; Maw, R; Zielhuis, G A; Haggard, M P
Abstract : Aims: To identify subgroups of children with otitis media with effusion (OME) that might benefit more than others from treatment with ventilation tubes. Methods: An individual patient data (IPD) meta-analysis on seven randomised controlled trials (n = 1234 children in all), focusing on interactions between treatment and baseline characteristics—hearing level (HL), history of acute otitis media, common colds, attending day-care, gender, age, socioeconomic status, siblings, season, passive smoking, and history of breast feeding. Outcome measures that could be studied were mean time spent with effusion (n = 557), mean hearing levels (n = 557 in studies that randomised children, and n = 180 in studies that randomised ears), and language development (n = 381). Results: In the trials that treated both ears the only significant interaction was between day-care and surgery, occurring where mean hearing level was the outcome measure. None of the other baseline variables showed an interaction effect with treatment that would justify subgrouping. In the trials that treated only one ear, the baseline hearing level showed a significant but not pervasive interaction with treatment—that is, only with a cut-off of 25 dB HL. Conclusions: The effects of conventional ventilation tubes in children studied so far are small and limited in duration. Observation (watchful waiting) therefore seems to be an adequate management strategy for most children with OME. Ventilation tubes might be used in young children that grow up in an environment with a high infection load (for example, children attending day-care), or in older children with a hearing level of 25 dB HL or greater in both ears persisting for at least 12 weeks.